Study of awareness and attitude of students of the Bogomolets national medical university to contraception - Boichenko , Olha; Moloshtan , Sophia; Zaychenko, Ganna; Hnatiuk, Valeriia (The Ukrainian Scientific Medical Youth Journal, 2024)
reproductive health care is recognised as one of the priority areas of health care in accordance with the United Nations World Assembly Resolution, which includes a set of preventive measures and services aimed at the well-being of families. Contraception is an important method of family planning and preserving the reproductive potential of the population by preventing abortions and related complications. In addition, according to the World Health Organisation, more than 1 million sexually transmitted infections are reported every day, most of which are asymptomatic but can be a factor in the development of both male and female infertility. Contraception is a well-known factor in preventing early pregnancy, stillbirths and complications associated with sexually transmitted diseases. That is why ensuring the reproductive health of young people is the key to the development of a healthy future generation. The aim of the study is to investigate the awareness and attitudes of students of different specialities and courses of the Bogomolets National Medical University towards contraceptive methods. The objects of the study were the most popular methods and means of contraception and the attitude of NMU students towards them. The anonymous questionnaire survey examined the attitude of students to such methods of contraception as: barrier contraceptives, interrupted intercourse, the method of "safe days", pharmacological contraception. Among the pharmacological methods, the respondents’ attitudes towards oral contraceptives, intrauterine devices, postcoital contraception, contraceptive patches, implants and injections were assessed. Respondents were asked to assess the effectiveness and convenience of these methods. The survey results showed that the level of students’ awareness of basic contraceptive methods was quite high. Among the proposed methods, respondents most often preferred barrier contraception. In addition, the data obtained was compared with the results of similar foreign studies, which showed that NMU students have a biased attitude and low level of trust in some methods that are highly effective according to the US Centers for Disease Control and Prevention protocols. The results of the survey substantiate the need to disseminate information about evidence-based methods and new contraceptive methods and their benefits when used among student youth.